THE CONTRIBUTION OF THE SCHOOL COMMITTEE IN THE IMPLEMENTATION OF SCHOOL-BASED MANAGEMENT IN MAN 1 TERNATE - Noho, Mubin; Mahmud, Moch. Natsir; Siraj, Arifuddin; Damopolii, Muljono (Jurnal Diskursus Islam, 2021)
The purpose of this study is to describe the reality of the contribution of the school committee in the implementation of school-based management in MAN 1 ternate. This study uses a qualitative research type of case study. The approach used is a pedagogical and managerial approach. The data is the focus of the research, namely improving the quality of education in the implementation of madrasa-based management, while the primary data sources are from the leadership, educators and education staff, committees and parents as well as documents related to efforts to improve the quality of education at MAN 1 Ternate. Secondary data sources in the form of data from various documents relevant to the research. Data collection techniques are observation, in-depth interviews, and documentation. Data analysis uses an inductive-conceptual approach, starting from empirical information and then constructing concepts or propositions. Furthermore, checking the validity of the data using the credibility and transferability test. The results showed the reality of implementing madrasah-based management at MAN 1 Ternate refers to the madrasah organization which can be measured in aspects madrasah committee. Meanwhile, the curriculum dimension in implementing madrasah-based management at MAN 1 Ternate in developing the curriculum is carried out with the madrasah head, all madrasah residents including the committee by adjusting the development and needs of students. Human resource management, the main requirements are aspects of educational qualifications, aspects of democratic, transparent and participatory managerial abilities. The sources of financing for the procurement and purchase of facilities and infrastructure are from DIPA, BOS funds and committee fees.